2006
DOI: 10.1104/pp.106.089003
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Sucrose Transporter AtSUC9. High-Affinity Transport Activity, Intragenic Control of Expression, and Early Flowering Mutant Phenotype

Abstract: (C.P.L.G., J.M.P.) AtSUC9 (At5g06170), a sucrose (Suc) transporter from Arabidopsis (Arabidopsis thaliana) L. Heynh., was expressed in Xenopus (Xenopus laevis) oocytes, and transport activity was analyzed. Compared to all other Suc transporters, AtSUC9 had an ultrahigh affinity for Suc (K 0.5 5 0.066 6 0.025 mM). AtSUC9 showed low substrate specificity, similar to AtSUC2 (At1g22710), and transported a wide range of glucosides, including helicin, salicin, arbutin, maltose, fraxin, esculin, turanose, and a-methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
203
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 142 publications
(213 citation statements)
references
References 43 publications
10
203
0
Order By: Relevance
“…S6, A and B). The possibility that a Suc transporter would be involved in coniferin transport (Chandran et al, 2003;Sivitz et al, 2007) was tested, but coniferin transport was barely influenced in the presence of Suc (Supplemental Fig. S6C).…”
Section: Discussionmentioning
confidence: 99%
“…S6, A and B). The possibility that a Suc transporter would be involved in coniferin transport (Chandran et al, 2003;Sivitz et al, 2007) was tested, but coniferin transport was barely influenced in the presence of Suc (Supplemental Fig. S6C).…”
Section: Discussionmentioning
confidence: 99%
“…As has been observed previously in dicots, in all the grass genomes available, there is only a single group 3 or 4 SUT gene (the two group 3 rice genes reported by Sauer [2007] are alleles from different cultivars). In dicots, the group 2 SUT genes underwent duplication and neofunctionalization (Baud et al, 2005;Sivitz et al, 2007Sivitz et al, , 2008, and in monocots, the group 1 SUTs similarly expanded (Fig. 2).…”
Section: Sutsmentioning
confidence: 96%
“…SUC5 could also act at the interface between the endosperm and embryo, since it is expressed in the endosperm and specifically the epidermis of the outer surface of the cotyledons (Supplemental Figure 7B) (Pommerrenig et al, 2013). Data from a SUC9 translational fusion to GUS indicated that SUC9 protein was also present in the embryo (Sivitz et al, 2007), although no transcriptional GUS activity was detected in seeds (Sauer et al, 2004). All these reports are in agreement with the observation that in vitro dissected embryos from the globular stage can reach the mature stage when grown in media supplemented with sucrose.…”
Section: Functional Model Of Sweets In Sucrose Translocation In Seedsmentioning
confidence: 99%